The impact of volatile organic compounds on ozone formation in the suburban area of Shanghai. (1st July 2020) - Zhang, Kun; Li, Li; Huang, Ling; Wang, Yangjun; Huo, Juntao; Duan, Yusen; Wang, Yuhang; Fu, Qingyan
Abstract: Volatile organic compounds (VOCs) are important precursors of photochemical smog and secondary organic aerosol (SOA). Quantitatively assessing the impact of VOCs on ozone (O3 ) formation could provide valuable information for the management of emission reduction and photochemical pollution control. In this study, we first figured out the ozone pollution episodes during 2018 at Dianshan Lake (DSL), which is located in the suburban area of Shanghai and is adjacent to three provinces of the YRD region. Then we analyzed continuous variation of O3 precursors and meteorological parameters. The online measurements show that the average volume mixing ratio of total VOCs (TVOC) was 15.41 ± 11.39 ppbv during the ozone pollution episodes, with the largest contribution from alkanes. To further identify the sources of VOCs, VOC concentration-weighted trajectories (CWT) were analyzed, and the results suggested that Zhejiang province could be the most important source region of VOCs at DSL. Analysis using an observation-base model showed that NO x and alkenes exhibited the most significant negative and positive influences on O3 formation, respectively. As for individual species, toluene and isoprene, whose S-weighted concentrations were 6.67 × 10 −2 and 5.94 × 10 −2  ppbv, respectively, were the key factors promoting the formation of O3 at DSL. To control the increase of O3, considering the policy feasibility, the abatement ratio of VOCs/NO x should be no less than 0.72. The findings advanced our knowledge of VOCs and their impact on O3 formation and will be helpful in formulating emission control strategies for coping with O3 pollution in YRD region. Highlights: Characteristics of ambient VOCs and their influences on O3 formation in a rural area downwind Shanghai were investigated. Strong photochemical losses of VOCs, especially alkenes, were found under high O x concentrations situations. Abatement ratio of VOCs/NOx should be no less than 0.72 to effectively control O3 .